Screening Ca concentration in staple food crops with energy dispersive x-ray fluorescence (EDXRF) - Guild, Georgia E.; Stangoulis, James (Springer, 2022)
Background and aims: Calcium deficiency is evident in populations worldwide and combating this could be addressed with the biofortification of staple crops. Consequently, identification of Ca concentration in breeding trials would be essential. Here we report the use of energy dispersive x-ray fluorescence (EDXRF) for the rapid screening of Ca concentration in seed samples. Methods: Grain samples of rice, wheat, pearl millet, bean, maize, and cowpea were provided from biofortification breeding programs and analysed with inductively coupled plasma – mass spectrometry (ICP-MS) to determine the reference Ca concentration. A set of samples were used to develop a Ca EDXRF calibration for each crop and another set of samples to validate the method. Results: The EDXRF results were comparable to the reference ICP-MS analysis with an average difference of < ± 5 mg kg-1 for all crops and RSD for duplicate analysis < 10% for all crops. Conclusions: EDXRF is suitable for the rapid analysis of Ca in bean, cowpea, wheat, pearl millet, maize and rice samples.